A survey‐based triage tool to identify patients potentially eligible for referral to an advanced heart failure centre. (27th June 2022) - Murphy, Laura; Giblin, Gerard T.; Starr, Neasa; Caples, Norma; Black, Regina; Halley, Carmel; McDonald, Kenneth; Joyce, Emer
Abstract: Aims: Accurate prevalence data for ambulatory advanced heart failure (HF) in European countries remains limited. This study was designed to identify the population of patients potentially eligible for referral for assessment for advanced surgical HF therapies to a National advanced HF and cardiac transplant centre. Methods and results: A survey comprising 13 potential clinical markers of advanced HF was developed, modified from the 'I NEED HELP' tool from the 2018 position statement of the Heart Failure Association of the European Society of Cardiology, and distributed to all HF clinic services (secondary and tertiary units) nationwide. Each HF clinic unit was asked to complete the survey on consecutive patients over a 3 month period fulfilling the following three criteria: (i) age <65 years; (ii) ejection fraction <40% and (iii) HF of >3 months duration. As a comparison, the number of actual referrals to the advanced HF clinic were also audited over a 9 month period. In all, 21 of 26 HF clinic units participated in the survey. Across the period of inclusion, 4950 all‐comer HF patients were seen across all sites. Of these, 375 (7.5%) fulfilled the inclusion criteria and were surveyed (74.4% male, median age 57 years [IQR: 11 years]). In total, 246 (66%) of the surveyed patients had ≥1 potential markers for advanced HF, representing just under 5% of the total all‐comer HF population seen across the same time period. Of these, 67 patients (27%) had ≥2, 48 (20%) had 3 and 40 (16%) had ≥4 potential markers. The most frequently noted markers were ≥1 HF hospitalization or unscheduled clinic review (56%), intolerance to renin‐angiotensin‐aldosterone system inhibitors due to hypotension or renal dysfunction (29%) and intolerance to beta‐blockers due to hypotension (27%). Almost one‐quarter of patients reported NYHA Class III or IV symptoms. During the advanced HF clinic audit, the number of patients actually referred to the advanced HF clinic during the same time period was <5% of this potentially eligible cohort. Conclusions: In this index prospective National survey, approximately 5% of an all‐comer routine HF clinic population and two‐thirds of a pre‐selected HF with reduced EF under 65 years cohort were found to have at least one clinical or biochemical marker suggesting advanced or impending advanced HF. Almost one‐quarter of patients in this chronic outpatient 'snapshot' population have NYHA III‐IV symptoms. This simple one‐page triage survey—modified from the 'I NEED HELP' tool—is useful to identify a population potentially eligible for referral to an advanced HF centre for assessment for advanced surgical therapies, thereby aiding resource and service planning.